Positron emission tomography imaging of cerebral glucose metabolism and type 1 cannabinoid receptor availability during temporal lobe epileptogenesis in the amygdala kindling model in rhesus monkeys. (17th April 2018) - Cleeren, Evy; Casteels, Cindy; Goffin, Karolien; Koole, Michel; Van Laere, Koen; Janssen, Peter; Van Paesschen, Wim
Summary: Objective: We investigated changes in the endocannabinoid system and glucose metabolism during temporal lobe epileptogenesis. Methods: Because it is rarely possible to study epileptogenesis in humans, we applied the electrical amygdala kindling model in nonhuman primates to image longitudinal changes in type 1 cannabinoid receptor (CB1R) binding and cerebral glucose metabolism. Two rhesus monkeys received [ 18 F]‐MK‐9470 and fluorodeoxyglucose–positron emission tomography ([ 18 F]‐FDG ‐PET) scans in each of the 4 kindling stages to quantify relative changes over time of CB1R binding and cerebral glucose metabolism in vivo. We constructed z ‐score images relative to a control group (n = 8), and considered only those changes measured in both kindled animals by calculating the binary conjunction image per kindling stage. Results: The seizure‐onset zone exhibited an increased CB1R binding and a decreased glucose metabolism, which both aggravated gradually in extent and intensity throughout kindling. The ipsilateral thalamus and insula showed hypometabolism that coincided with an increase and a decrease in CB1R binding, respectively. These changes also became gradually more severe throughout kindling and overlapped with ictal perfusion changes during the final stage of amygdala kindling, with hyperperfusion in the ipsilateral thalamus and hypoperfusion in the ipsilateral insula. Significance: The observed changes in CB1R binding may reflect a combination of a protective mechanism of neurons against seizure activity that becomes stronger over time to combat more severe seizures, and on the other hand, a process of epileptogenesis that facilitates seizure activity and generalization, depending on the cell type involved in those specific regions. This study provides unique evidence that the CB1R is dynamically and progressively involved from the start of mesial temporal lobe epileptogenesis.